2022
DOI: 10.1021/acsami.2c12589
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Bacterial Behavior by Light and Magnetism Mediated by Mesoporous Silica-Coated MnFe2O4@CoFe2O4 Nanoparticles

Abstract: Unicellular bacterial cells exhibit diverse population behaviors (i.e., aggregation, dispersion, directed assembly, biofilm formation, etc.) to facilitate communication and cooperation. Suitable bacterial behaviors are required for efficient nutrient uptake, cell recycling, and stress response for environmental and industrial application of bacterial populations. However, it remains a great challenge to artificially control bacterial behaviors because of complicated genetic and biochemical mechanisms. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…[174] In addition, the hydrophilic, biocompatible, and non-toxic properties of Si NPs make them excellent carriers for various drugs. [175] Many studies have shown that RES promotes the recovery of nerve function by regulating oxidative stress, inflammation, apoptosis, and glial scar formation after SCI. [176] Jiang et al [177] used plasma complex component-functionalized manganesedoped silica NPs (PMMSN) as targeted drug carriers for RES to transport drugs across the BSCB.…”
Section: Silica Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…[174] In addition, the hydrophilic, biocompatible, and non-toxic properties of Si NPs make them excellent carriers for various drugs. [175] Many studies have shown that RES promotes the recovery of nerve function by regulating oxidative stress, inflammation, apoptosis, and glial scar formation after SCI. [176] Jiang et al [177] used plasma complex component-functionalized manganesedoped silica NPs (PMMSN) as targeted drug carriers for RES to transport drugs across the BSCB.…”
Section: Silica Nanoparticlesmentioning
confidence: 99%
“…[ 174 ] In addition, the hydrophilic, biocompatible, and non‐toxic properties of Si NPs make them excellent carriers for various drugs. [ 175 ]…”
Section: Nanoparticle‐based Multimodal Strategy For Treating Scimentioning
confidence: 99%